Implementasi Multiple Port knocking dan Port blocking Untuk Peningkatan Keamanan Hak Akses Administrator Pada Router board Mikrotik - Dian Novianto; Yohanes Setiawan Japriadi; Lukas Tommy (STMIK Pringsewu, 2023)
Access rights to network systems are things that must be limited because they involve the operations of an organization. Making a password alone is not enough, because there is a brute force attack that can guess the password, so that other people who are not entitled, can get access rights to the network system. Therefore it is necessary to create a mechanism to avoid brute force attacks to secure access rights, especially administrator access rights. One combinations of method that can be used is port knocking and port blocking, using 3 combinations of port knocking and port blocking will increase the chances of a brute force attack failing because failure to knock will activate the firewall to enable port blocking. For the application of this method, a tool is needed in the form of an RB951Ui-2nD routerboard, besides that, a network system development method is needed which is a reference in system development, in this study the method used is PPDIOO which consists of Prepare, Plan, Design, Implement, Operate, and Optimize. And also some supporting tools for the development of the system in the form of Unified Modeling Language (UML). The result of applying 3 combinations of multiple port knocking, produces 6 opportunities that can strengthen the router's access security system from brute force attacks.